Engaging in Twitter thematic content analysis to understand the political messages of the Jokowi-Amin and Prabowo-Sandi success teams in the 2019 Indonesian presidential election - Kulau, Febriansyah; Setiawan, Benni; Hastasari, Chatia (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This article discusses religious and religious symbols narrated as political commodities in the 2019 presidential election on the twitter platform. The battle for narratives in the 2019 Indonesian presidential election was colored by the use of these issues on social media, this has led to increased sensitivity between religions and increasing issues of intolerance. For this reason this research has been conducted to investigate the categories of political messages narrated in tweets during the seven months of the 2019 presidential election campaign. Twitter, which was published on 23 September 2018 to 13 April 2019. based on the findings of this study, it shows that the success team of the two candidate pairs in narrating religious symbols and religious symbols is divided into 6 message categories. The message categories are Commodification of Religious Greetings, Clothing as a Religious Symbol, Title as a Religious Symbol, Salat and Nyekar as Political Commodities, An Expression of Gratitude as Political Commodities, House of Worship as a Place for Political Campaign.